Central Asian Literature and Shaykhzoda - Javlon Jovliev (Genius Journals, 2023)
The spirit and the history of the nation are reflected in the literature. Both the past and the future live in the literature. So, its impossible to imagine the identity and the history of the continent without literature. World famous Uzbek and Azarbayjan poet, scientist, interpretor Maksud Sheikhzoda also connected the Centeral Asia with Luterature. As you study his manuscripts at the Alisher Navoi State Literature Museum of the Academy of Sciences of Uzbekistan, you can see this.
Keywords: manuscript; text; dramaturgy; creative laboratory